Preparation method of multi-walled carbon nanotube loaded on surface of iron-containing waste residue micro powder

By magnetizing the iron-containing waste slag and mixing it with ferrocene and other substances, and then microwave processing, multi-wall carbon nanotubes loaded on the surface of the iron-containing waste slag micropowder, the problem of poor dispersion in cement-based materials in the prior art is solved, and the mechanical and durability of the material is significantly improved.

CN119774592APending Publication Date: 2025-04-08NANCHANG INST OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411955261.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing process for preparing multi-wall carbon nanotubes is complex, the conditions are harsh, and the dispersion is poor in cement-based grouting materials.

Method used

By magnetizing and crushing the iron-containing waste slag into micropowder, then evenly mixing it with ferrocene or its derivatives, additional carbon sources and arc inducer, and then microwave treatment, the arc inducer produces an arc effect under the action of microwave, making the system temperature instantly reach 1000℃, catalyzing the generation of multi-wall carbon nanotubes and loading it on the surface of the iron-containing waste slag micropowder.

Benefits of technology

The good dispersion and better compatibility of multi-wall carbon nanotubes in cement-based materials are achieved, and the mechanical properties and durability of cement-based materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774592A_ABST
    Figure CN119774592A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a multi-walled carbon nanotube loaded on the surface of iron-containing waste residue, and belongs to the technical field of material preparation. According to the method, after being magnetized, crushed and ground, the iron-containing waste residues are mixed with ferrocene or a derivative thereof, meanwhile, an additional carbon source and an electric arc inducer are doped, then microwave treatment is conducted, the electric arc inducer generates an electric arc effect under the action of microwaves, the temperature in a system is made to reach up to 1000 DEG C instantly, and the iron-containing waste residues are obtained. Ferrocene or a derivative thereof is decomposed into nano-iron atoms and hydrocarbon compounds at high temperature, the nano-iron atoms are adsorbed on the surface of iron-containing waste residues under the action of magnetic force to generate an iron-carbon phase, the hydrocarbon compounds are catalyzed to generate multi-walled carbon nanotubes, and the multi-walled carbon nanotubes are loaded on the surface of magnetized iron-containing waste residue micro-powder, so that the multi-walled carbon nanotubes are formed. The introduction of an extra carbon source promotes the quality of the grown multi-walled carbon nanotubes to be more uniform to a certain extent. The preparation method disclosed by the invention is simple and easy to implement and low in cost, has good dispersity in a cement-based material, and can be applied to industries such as civil engineering on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material preparation, and in particular to a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag micropowder. Background Art

[0002] As a nano-scale super fiber material, multi-walled carbon nanotubes have relatively high modulus and strength. Its Young's modulus is about 1000GPa, and its tensile strength is about 30GPa, which are 10 to 20 times that of carbon fiber. Its elongation at break reaches 18%, and its bending strength reaches 14GPa, while its weight density is only 1 / 7 to 1 / 6 of that of steel. Adding a certain amount of multi-walled carbon nanotubes to cement-based grouting materials can play a nano-filling effect and a nano-nucleation effect, promote cement hydration, and play a bridging role in microcracks, which can effectively improve the mechanical properties and durability of cement-based materials.

[0003] Multi-walled carbon nanotubes have a large specific surface area and are easy to agglomerate. In the pore solution of cement-based materials, which is an alkaline solution with a pH value greater than 12, their surface functional groups are easily ionized, resulting in reduced hydrophilicity. They are easy to agglomerate in cement-based materials and have poor dispersibility. This has an adverse effect on the development of the working performance, mechanical properties and durability of cement-based materials.

[0004] At present, the methods for preparing multi-walled carbon nanotubes include chemical deposition, arc method and laser discharge method. These methods require expensive equipment, harsh conditions and complicated steps. The prepared multi-walled carbon nanotubes have poor dispersibility in cement-based materials, which has a great impact on the development of mechanical properties and durability of cement-based materials. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag powder, aiming to solve the problems of complex existing preparation process of multi-walled carbon nanotubes, harsh conditions and poor dispersion in cement-based grouting materials.

[0006] The present application provides a method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag micropowder, comprising the following steps:

[0007] S1. The iron-containing waste slag is placed in an inert gas for magnetization roasting to obtain a magnetized iron-containing waste slag;

[0008] S2. The magnetized iron-containing waste slag is crushed and ground to obtain a magnetized iron-containing waste slag powder;

[0009] S3. The magnetized iron-containing waste slag powder is uniformly mixed with ferrocene or a derivative thereof, an additional carbon source and an arc inducing agent to obtain a mixture;

[0010] S4. The mixture is subjected to microwave treatment to obtain multi-walled carbon nanotubes supported on the surface of the iron-containing waste slag powder.

[0011] In the technical scheme of the embodiment of the present application, the iron-containing waste slag is magnetized, crushed and ground to obtain magnetized iron-containing waste slag powder, which is then mixed with ferrocene or its derivatives, added with additional carbon sources and arc inducers, and then microwaved. The arc inducer produces an arc effect under the action of microwaves, so that the temperature in the system instantly reaches 1000°C, and ferrocene or its derivatives decompose into nano-iron atoms and hydrocarbon compounds at high temperature. The nano-iron atoms are uniformly adsorbed on the surface of the iron-containing waste slag under the action of magnetic force and generate an iron-carbon phase, which catalyzes the hydrocarbon compounds to generate multi-walled carbon nanotubes, thereby uniformly growing multi-walled carbon nanotubes on the surface of the iron-containing waste slag powder that originally could not grow carbon nanotubes, and mixing the obtained multi-walled carbon nanotubes loaded on the surface of the iron-containing waste slag powder with cement-based materials, which can effectively improve the dispersibility of the multi-walled carbon nanotubes in cement-based materials and make them more compatible with cement-based materials. At the same time, based on the preparation of multi-walled carbon nanotubes using ferrocene or its derivatives, the present application can further assist the growth of multi-walled carbon nanotubes during the high-temperature instantaneous reaction by additionally introducing a carbon source, thereby forming multi-walled carbon nanotubes with more uniform quality in a short time to improve the performance of cement-based materials.

[0012] In some embodiments, in step S3, the mass ratio of the magnetized iron-containing waste slag powder to ferrocene or its derivatives is 0.42 to 1.25:1.

[0013] In this embodiment, a specific ratio of magnetized iron-containing waste slag powder is mixed with ferrocene or its derivatives, which not only enables the magnetized iron-containing waste slag powder to be fully contacted with ferrocene or its derivatives, but also the nano-iron atoms generated by the subsequent decomposition of ferrocene or its derivatives can be effectively adsorbed on the surface of the magnetized iron-containing waste slag powder.

[0014] In some embodiments, in step S4, the microwave treatment is microwave heating in a microwave oven; the power of the microwave treatment is 700-900 W; the frequency of the microwave treatment is 2.2-2.6 GHZ, and the time of the microwave treatment is 50-90 s.

[0015] In this embodiment, microwave treatment is used to generate a high temperature in the mixture system, thereby providing conditions for the complete decomposition of ferrocene or its derivatives. If the microwave treatment time is too short, the decomposition of ferrocene or its derivatives will not be complete. If the microwave treatment time is too long, carbon monoxide will be generated under the action of high temperature, leading to de-carbon nanotube formation, thereby reducing the carbon nanotubes loaded on the surface of the iron-containing waste slag powder.

[0016] In some embodiments, in step S1, the magnetization calcination method is a suspension method; the calcination temperature is 800-1000° C.; and the calcination time is 20-30 seconds.

[0017] In this embodiment, the iron-containing waste slag powder is magnetized by high-temperature calcination, which provides conditions for the growth of nano-iron atoms generated by the subsequent decomposition of ferrocene or its derivatives on its surface.

[0018] In some embodiments, in step S3, the additional carbon source is cyclohexane, and the amount thereof is 0.2-0.5% by weight of ferrocene or its derivatives.

[0019] In this embodiment, the addition of additional carbon source plays a role of supplementing carbon source to a certain extent, which is beneficial to the high-temperature decomposition of ferrocene or its derivatives to produce hydrocarbon compounds, and then generate multi-walled carbon nanotubes with more uniform quality in a short time, thereby effectively improving the performance of cement-based materials.

[0020] In some embodiments, in step S3, the arc inducer is carbon fiber, and the length of the carbon fiber is 5 mm to 15 mm.

[0021] In this embodiment, by adding an arc inducing agent, an arc effect can be generated under the action of microwaves, so that the temperature in the system instantly reaches 1000°C.

[0022] In some embodiments, in step S1, the iron-containing waste slag is waste slag containing elemental iron and / or iron oxides.

[0023] In this embodiment, the iron element and / or iron oxide contained in the waste slag can be magnetized to provide a carrier for the growth of multi-walled carbon nanotubes on the surface thereof.

[0024] In some embodiments, the waste slag containing elemental iron and / or iron oxides is one or more of steel slag, magnetite, hematite, limonite, and siderite.

[0025] In this embodiment, the waste slags are all wastes from steelmaking or mineral processing, and the comprehensive utilization rate of these waste slags can be improved.

[0026] In some embodiments, in step S2, the particle size of the magnetized iron-containing waste slag powder is 10 to 100 μm.

[0027] In this embodiment, the particle size distribution of the iron-containing waste slag is controlled within a range of 10 μm to 100 μm, which is beneficial for the prepared carbon nanotubes loaded on the surface of the iron-containing waste slag to have better compatibility in cement-based materials.

[0028] In some embodiments, in step S4, the mixing method is stirring with a rotary stirrer; the stirring rate is 80 to 120 rpm; and the stirring time is 3 to 5 min.

[0029] In this embodiment, the raw materials are fully mixed by stirring.

[0030] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 This is a SEM image of the multi-walled carbon nanotubes prepared in Example 1 and loaded on the surface of the slag micropowder.

[0033] Figure 2 These are SEM images of the multi-walled carbon nanotubes loaded on the surface of steel slag powder prepared in Examples 2-3 and Comparative Examples 1-2.

[0034] Figure 3 These are SEM images of the multi-walled carbon nanotubes loaded on the surface of steel slag powder prepared in Examples 4-5 and Comparative Examples 3-4.

[0035] Figure 4 This is the SEM image of the multi-walled carbon nanotubes loaded on the surface of steel slag powder prepared in Comparative Example 5.

[0036] Figure 5 This is the SEM image of the multi-walled carbon nanotubes loaded on the surface of steel slag powder prepared in Comparative Examples 7-8. DETAILED DESCRIPTION

[0037] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms "including" and "having" and any variations thereof used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0039] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0040] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0041] In order to solve the problems of complicated processes, harsh conditions and poor dispersion in cement-based grouting materials for preparing multi-walled carbon nanotubes, the present application provides a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag powder. The iron-containing waste slag is magnetized, crushed and ground to obtain magnetized iron-containing waste slag powder, which is then mixed with ferrocene or its derivatives, added with carbon sources and arc inducers, and then microwaved. The arc inducers produce arc effects under the action of microwaves, so that the temperature in the system instantly reaches 1000°C, and ferrocene or its derivatives are decomposed into nano-iron atoms and hydrocarbon compounds at high temperatures. The nano-iron atoms are uniformly adsorbed on the surface of the iron-containing waste slag under the action of magnetic force and generate iron-carbon phases, catalyzing hydrocarbon compounds to generate multi-walled carbon nanotubes, and loaded on the surface of the magnetized iron-containing waste slag powder. The introduction of additional carbon sources provides additional carbon sources for the growth of multi-walled carbon nanotubes, promotes the quality of the grown multi-walled carbon nanotubes to be more uniform, and can bring better enhancement effects when added to fillers. The preparation method of the invention is simple and easy, has low cost and has good dispersibility in cement-based materials under alkaline environment, and can be mass-produced for use in industries such as civil engineering.

[0042] The present application provides a method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag micropowder, comprising the following steps:

[0043] S1. The iron-containing waste slag is placed in an inert gas for magnetization roasting to obtain a magnetized iron-containing waste slag;

[0044] S2. The magnetized iron-containing waste slag is crushed and ground to obtain a magnetized iron-containing waste slag powder;

[0045] S3. The magnetized iron-containing waste slag powder is uniformly mixed with ferrocene or a derivative thereof, an additional carbon source and an arc inducing agent to obtain a mixture;

[0046] S4. The mixture is subjected to microwave treatment to obtain multi-walled carbon nanotubes supported on the surface of the iron-containing waste slag powder.

[0047] In the technical scheme of the embodiment of the present application, the iron-containing waste slag is magnetized, crushed and ground to obtain magnetized iron-containing waste slag powder, which is then mixed with ferrocene or its derivatives, added with additional carbon sources and arc inducers, and then microwaved. The arc inducer produces an arc effect under the action of microwaves, so that the temperature in the system instantly reaches 1000°C, and ferrocene or its derivatives decompose into nano-iron atoms and hydrocarbon compounds at high temperature. The nano-iron atoms are uniformly adsorbed on the surface of the iron-containing waste slag under the action of magnetic force and generate an iron-carbon phase, which catalyzes the hydrocarbon compounds to generate multi-walled carbon nanotubes, thereby uniformly growing multi-walled carbon nanotubes on the surface of the iron-containing waste slag powder that originally could not grow carbon nanotubes, and mixing the obtained multi-walled carbon nanotubes loaded on the surface of the iron-containing waste slag powder with cement-based materials, which can effectively improve the dispersibility of the multi-walled carbon nanotubes in cement-based materials and make them more compatible with cement-based materials. At the same time, based on the use of ferrocene or its derivatives to prepare multi-walled carbon nanotubes, the present application can further assist the growth of multi-walled carbon nanotubes during high-temperature instantaneous reaction by introducing additional carbon sources, thereby forming multi-walled carbon nanotubes with more uniform quality in a short time to improve the performance of cement-based materials.

[0048] Furthermore, in some embodiments, in step S3, the mass ratio of the magnetized iron-containing waste slag powder to ferrocene or its derivatives is 0.42-1.25:1.

[0049] In the technical solution of the embodiment of the present application, a specific proportion of magnetized iron-containing waste slag micropowder is mixed with ferrocene or its derivatives, which not only enables the magnetized iron-containing waste slag micropowder to be fully contacted with ferrocene or its derivatives, but also the nano-iron atoms generated by the subsequent decomposition of ferrocene or its derivatives can be effectively adsorbed on the surface of the magnetized iron-containing waste slag micropowder.

[0050] Further, in some embodiments, in step S4, the microwave treatment is microwave heating in a microwave oven; the power of the microwave treatment is 700-900 W; the frequency of the microwave treatment is 2.2-2.6 GHZ, and the time of the microwave treatment is 50-90 s.

[0051] In the technical solution of the embodiment of the present application, the mixture system is subjected to microwave treatment to generate high temperature, thereby providing conditions for the sufficient decomposition of ferrocene or its derivatives; if the microwave treatment time is too short, the decomposition of ferrocene or its derivatives will be insufficient, and if the microwave treatment time is too long, de-carbon nanotube formation will occur, resulting in less carbon nanotubes loaded on the surface of the iron-containing waste slag powder.

[0052] Furthermore, in some embodiments, in step S1, the magnetization calcination is carried out by a suspension method; the calcination temperature is 800 to 1000° C.; and the calcination time is 20 to 30 seconds.

[0053] In the technical solution of the embodiment of the present application, the iron-containing waste slag powder is magnetized by high-temperature roasting, providing conditions for the growth of nano-iron atoms produced by the subsequent decomposition of ferrocene or its derivatives on its surface.

[0054] Furthermore, in some embodiments, in step S3, the carbon source is cyclohexane, the amount used is 0.2-0.5% of the mass of ferrocene or its derivatives, and the addition method is dropwise addition with a pipette.

[0055] In the technical solution of the embodiment of the present application, the addition of additional carbon source plays a role in supplementing the carbon source to a certain extent, which is beneficial to the high-temperature decomposition of ferrocene or its derivatives to produce hydrocarbon compounds, and then generate multi-walled carbon nanotubes with more uniform quality in a short period of time, thereby effectively improving the performance of cement-based materials.

[0056] Furthermore, in some embodiments, in step S3, the arc inducer is carbon fiber, the mass of which is 0.2% to 0.3% of ferrocene and its derivatives, and the length of which is 5 mm to 15 mm.

[0057] In the technical solution of the embodiment of the present application, by adding an arc inducing agent, an arc effect can be generated under the action of microwaves, so that the temperature in the system instantly reaches 1000°C.

[0058] Furthermore, in some embodiments, in step S1, the iron-containing waste slag is waste slag containing iron element and / or iron oxide.

[0059] In the technical solution of the embodiment of the present application, the iron element and / or iron oxide contained in the waste slag can be magnetized to provide a carrier for the growth of multi-walled carbon nanotubes on its surface.

[0060] Furthermore, in some embodiments, the waste slag containing elemental iron and / or iron oxides is one or more of steel slag, magnetite, hematite, limonite, and siderite.

[0061] In the technical solution of the embodiment of the present application, the waste slags are all wastes from steelmaking or mineral processing, which can improve the comprehensive utilization rate of these waste slags.

[0062] Furthermore, in some embodiments, in step S2, the crushing is performed in a crusher for 1 to 2 hours; the grinding is performed in a planetary ball mill for 1.5 to 2.5 hours.

[0063] In the technical solution of the embodiment of the present application, the particle size distribution of the iron-containing waste slag is controlled to be 10 μm to 100 μm by crushing and grinding.

[0064] Furthermore, in some embodiments, in step S2, the particle size of the magnetized iron-containing waste slag powder is 10 to 100 μm.

[0065] In the technical solution of the embodiment of the present application, the particle size distribution of the iron-containing waste slag is controlled within a range of 10 μm to 100 μm, which is conducive to the prepared carbon nanotubes loaded on the surface of the iron-containing waste slag having better compatibility in cement-based materials.

[0066] Furthermore, in some embodiments, in step S4, the mixing method is stirring; the stirring rate is 80 to 120 rpm; and the stirring time is 3 to 5 min.

[0067] In the technical solution of the embodiment of the present application, the raw materials can be fully mixed by stirring.

[0068] Furthermore, in some embodiments, the multi-walled carbon nanotubes supported on the surface of the iron-containing waste slag powder prepared in step S4 are cooled and sieved; the cooling time is 5 to 10 minutes.

[0069] In the technical solution of the embodiment of the present application, the carbon fibers in the mixture can be removed by screening.

[0070] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0071] Example 1

[0072] This embodiment provides a method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder, which specifically includes the following steps:

[0073] (1) The steel slag is magnetized and roasted for 20 seconds by a suspension method to magnetize the steel slag, and then the magnetized steel slag is crushed in a crusher for 1 hour and ground in a planetary ball mill for 2 hours to obtain magnetized steel slag powder.

[0074] (2) Take 0.67 g of magnetized steel slag powder, 1 g of ferrocene and 0.3 g of carbon fiber with a length of 5 mm and place them in a crucible with a lid. At the same time, use a pipette to drop 0.005 g of cyclohexane into the crucible, and then stir in a mixer at a stirring speed of 100 rpm for 5 min.

[0075] (3) The crucible was placed in a household microwave oven with a power of 800 W and a microwave frequency of 2.4 GHZ. After microwave heating for 70 seconds, the crucible was taken out, cooled for 10 minutes, and then sieved. The resulting black powder was multi-walled carbon nanotubes loaded on the surface of the steel slag powder.

[0076] The SEM image of the multi-walled carbon nanotubes loaded on the surface of the steel slag powder prepared in this example is as follows: Figure 1 shown.

[0077] Depend on Figure 1 It can be seen that the multi-walled carbon nanotubes loaded on the surface of the steel slag powder prepared in this embodiment are uniformly grown on the surface of the steel slag powder.

[0078] Examples 2 to 3 and Comparative Examples 1 to 2

[0079] Examples 2 to 3 and Comparative Examples 1 to 2 respectively provide a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag powder. Compared with Example 1, the difference is that the amount of steel slag powder in step (2) is different. The specific amount is shown in Table 1. The other steps are roughly the same as Example 1 and will not be repeated here.

[0080] Table 1 Amount of steel slag powder in Examples 2 to 3 and Comparative Examples 1 to 2

[0081] Example / Comparative Example Example 2 Example 3 Comparative Example 1 Comparative Example 2 Dosage(g) 0.42 1.25 0.25 1.5

[0082] The SEM images of the multi-walled carbon nanotubes loaded on the surface of the steel slag powder prepared in Examples 2-3 and Comparative Examples 1-2 are as follows: Figure 2 shown.

[0083] Depend on Figure 2 It can be seen from the SEM images of Examples 2 to 3 that when the ratio of steel slag powder to ferrocene is 0.42 to 1.25:1, carbon nanotubes grow uniformly on the surface of the steel slag powder; it can be seen from the SEM images of Comparative Examples 1 to 2 that when there is too much or too little steel slag powder, the growth of carbon nanotubes on the surface of the steel slag powder will be affected.

[0084] Examples 4 to 5 and Comparative Examples 3 to 4

[0085] Examples 4 to 5 and Comparative Examples 3 to 4 respectively provide a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag powder. Compared with Example 2, the difference is that the time of microwave treatment in step (3) is different, as shown in Table 2. The other steps are roughly the same as those in Example 1 and will not be repeated here.

[0086] Table 2 Microwave treatment time in Examples 4 to 5 and Comparative Examples 3 to 4

[0087] Example / Comparative Example Example 4 Example 5 Comparative Example 3 Comparative Example 4 Microwave treatment time (s) 50 90 40 100

[0088] The SEM images of the multi-walled carbon nanotubes loaded on the surface of the steel slag powder prepared in Examples 4-5 and Comparative Examples 3-4 are as follows: Figure 3 shown.

[0089] Depend on Figure 3 It can be seen from the SEM images of Examples 4 to 5 that when the microwave treatment time is 50 to 90 s, carbon nanotubes grow uniformly on the surface of the steel slag powder; it can be seen from the SEM images of Comparative Examples 3 to 4 that when the microwave treatment time is too short or too long, it will affect the growth of carbon nanotubes on the surface of the steel slag powder.

[0090] Comparative Example 5

[0091] This comparative example provides a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag powder. Compared with Example 1, the difference is that the steel slag in step (1) has not been subjected to magnetization roasting treatment, and the other steps are roughly the same as Example 1 and will not be repeated here.

[0092] The SEM image of the multi-walled carbon nanotubes loaded on the surface of the steel slag powder prepared in this comparative example is as follows: Figure 4 shown.

[0093] Depend on Figure 4 It can be seen from the SEM image of Comparative Example 5 that there is almost no growth of multi-walled carbon nanotubes on the surface of the steel slag powder that has not been magnetized.

[0094] The multi-walled carbon nanotubes loaded on the surface of steel slag powder prepared in Examples 1 to 5 and Comparative Examples 1 to 5 were added to cement mortar, and the amount of the multi-walled carbon nanotubes loaded on the surface of steel slag powder was 0.4%. The mix ratio of cement mortar was: cement: fly ash: standard sand: water: water reducing agent = 716: 235: 1350: 280: 8.

[0095] Among them, the cement is PO 42.5 cement, the water is tap water, and the water reducer is polycarboxylic acid high-efficiency water reducer.

[0096] Comparative Example 6

[0097] In this comparative example, commercially available carbon nanotubes were added to cement mortar, and the amount of carbon nanotubes added was 0.4%. The mix ratio of cement mortar was: cement: fly ash: standard sand: water: water reducing agent = 716: 235: 1350: 280: 8.

[0098] Among them, the cement is PO 42.5 cement, the water is tap water, and the water reducer is polycarboxylic acid high-efficiency water reducer.

[0099] According to the cement mortar fluidity determination method of GB / T 2419-2005, the properties of the cement mortar pastes containing carbon nanotubes prepared in Examples 1 to 5 and Comparative Examples 1 to 6 were tested. The test results are shown in Table 3.

[0100] Table 3 Performance test results of cement mortar slurries containing carbon nanotubes in Examples 1 to 5 and Comparative Examples 1 to 6

[0101]

[0102]

[0103] It can be seen from the test results of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 3 that when the ratio of steel slag powder to ferrocene in the carbon nanotubes loaded on the surface of steel slag powder is 0.42 to 1.25:1, the expansion of the cement mortar slurry containing carbon nanotubes is good, because the carbon nanotubes loaded on the surface of steel slag powder have good dispersibility in cement mortar. It can be seen from the test results of Examples 4 to 5 and Comparative Examples 3 to 4 that when the microwave treatment time is 50 to 90 seconds, the expansion of the cement mortar is good, because the carbon nanotubes loaded on the surface of steel slag powder have good dispersibility in cement mortar. In Comparative Examples 5 to 6, the expansion of the cement mortar slurry containing carbon nanotubes is poorer than that of Examples 1 to 5, indicating that the carbon nanotubes loaded on the surface of steel slag powder prepared in this application can improve the dispersibility of carbon nanotubes in mortar sand.

[0104] Comparative Examples 7 to 8

[0105] Comparative Examples 7 to 8 provide a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag powder. Compared with Example 1, the difference is that in Comparative Example 7, cyclohexane is not added in step (2), and in Comparative Example 8, 0.01 g of cyclohexane is added in step (2). The other steps are roughly the same as in Example 1 and are not repeated here.

[0106] The SEM images of the multi-walled carbon nanotubes loaded on the surface of the steel slag powder prepared in Comparative Examples 7 to 8 are as follows: Figure 5 shown.

[0107] Depend on Figure 5 It can be seen that the addition of additional carbon source has a certain influence on the uniformity of the quality of carbon nanotubes growing on the surface of steel slag powder.

[0108] In summary, the present application provides a method for preparing multi-walled carbon nanotubes loaded on the surface of iron-containing waste slag powder. The iron-containing waste slag is magnetized, crushed, and ground to obtain magnetized iron-containing waste slag powder, which is then mixed with ferrocene or its derivatives, and at the same time, a carbon source and an arc inducer are added, and then microwaved. The arc inducer produces an arc effect under the action of microwaves, so that the temperature in the system instantly reaches 1000°C, and ferrocene or its derivatives are decomposed into nano-iron atoms and hydrocarbon compounds at high temperature. The nano-iron atoms are uniformly adsorbed on the surface of the iron-containing waste slag under the action of magnetic force and generate an iron-carbon phase, catalyzing hydrocarbon compounds to generate multi-walled carbon nanotubes, and loaded on the surface of the magnetized iron-containing waste slag powder. The introduction of an additional carbon source provides an additional carbon source for the growth of multi-walled carbon nanotubes, promotes the quality of the grown multi-walled carbon nanotubes to be more uniform, and can bring better enhancement effects when added to fillers. The preparation method of the invention is simple and easy, has low cost and has good dispersibility in cement-based materials under alkaline environment, and can be mass-produced for use in industries such as civil engineering.

[0109] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag, characterized in that: The following steps are involved: S1. The iron-containing waste slag is placed in an inert gas for magnetization roasting to obtain a magnetized iron-containing waste slag; S2. The magnetized iron-containing waste slag is crushed and ground to obtain a magnetized iron-containing waste slag powder; S3. The magnetized iron-containing waste slag powder is uniformly mixed with ferrocene or a derivative thereof, an additional carbon source and an arc inducing agent to obtain a mixture; S4. The mixture is subjected to microwave treatment to obtain multi-walled carbon nanotubes supported on the surface of the iron-containing waste slag powder.

2. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S3, the mass ratio of the magnetized iron-containing waste slag powder to ferrocene or its derivatives is 0.42-1.25:

1.

3. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S4, the microwave treatment is microwave heating in a microwave oven; the power of the microwave treatment is 700-900W; the frequency of the microwave treatment is 2.2-2.6GHZ, and the time of the microwave treatment is 50-90s.

4. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S1, the magnetization calcination is carried out by a suspension method; the calcination temperature is 800 to 1000° C.; and the calcination time is 20 to 30 seconds.

5. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S3, the additional carbon source is cyclohexane, and the amount used is 0.2-0.5% of the mass of ferrocene or its derivatives.

6. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S3, the arc inducer is carbon fiber, and the length of the carbon fiber is 5 to 15 mm.

7. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S1, the iron-containing waste slag is waste slag containing iron element and / or iron oxide.

8. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 7, characterized in that: The waste slag containing elemental iron and / or iron oxide is one or more of steel slag, magnetite, hematite, limonite and siderite.

9. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S2, the particle size of the magnetized iron-containing waste slag powder is 10 to 100 μm.

10. The method for preparing multi-walled carbon nanotubes supported on the surface of iron-containing waste slag powder according to claim 1, characterized in that: In step S3, the mixing method is stirring; the stirring rate is 80 to 120 rpm; and the stirring time is 3 to 5 minutes.

Citation Information

Patent Citations

  • Ultra-long carbon nanotube preparation device and preparation method

    CN105731415A

  • Preparation method for carbon nanometer pipe

    CN106495130A

  • Method for preparing carbon nano tube by means of microwaves

    CN106744818A

  • Low-walled carbon nanotube fiber bundle and preparation process thereof

    CN114477141A

  • Method for preparing three-dimensional carbon nanotube wave-absorbing material based on steel slag catalysis

    CN117361508A